Biomechanics of the human body - Okuno, Emico (Undergraduate lecture notes in physics, 2014)
Biomechanics of the Human Body teaches basic physics concepts using examples and problems based on the human body. The reader will learn how the laws of mechanics may help to understand the conditions of the static and dynamic equilibrium of one of the marvels of nature: the human body.The mathematical language used in physics has always been pointed out as responsible for students' difficulties. So each concept given is followed by explanatory examples, with subsequent application and fixation exercises. It is a richly illustrated book that facilitates the comprehension of presented concepts.Biomechanics of the Human Body will be useful to students of physical and occupational therapy, physical education, the life sciences, and health care professionals who deal with biomechanics. This book is also recommended for sport practitioners as well as the general reader interested in the mechanics of the human body.--